The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1002/jmv.1890400308
|View full text |Cite
|
Sign up to set email alerts
|

Lassa virus activity in Guinea: Distribution of human antiviral antibody defined using enzyme‐linked immunosorbent assay with recombinant antigen

Abstract: More than 3,100 households in 27 selected villages distributed in the main geographic regions of Guinea were surveyed for the presence of Lassa virus-specific IgG antibodies (LVA), using an enzyme-linked immunosorbent assay (ELISA) with Lassa virus nucleocapsid protein expressed in insect cells infected with a recombinant baculovirus as antigen. The highest prevalence of LVA (25-55%) was found among inhabitants of tropical secondary forest (areas near Gueckedou, Yomou, and Lola) and guinea savannah (Faranah an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
78
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(86 citation statements)
references
References 22 publications
(10 reference statements)
2
78
1
1
Order By: Relevance
“…As suggested by murine experiments, ingestion of arenavirus [Rai et al, 1997] and of vectors expressing viral antigens [Djavani et al, 2000[Djavani et al, , 2001] provides immunity to lethal disease. Circumstantial evidence for mucosal immunity through virus ingestion comes from field observations: many individuals living in close contact with rodents and ingesting rodent-contaminated food are seropositive for Lassa virus but have never experienced Lassa fever disease [ter Meulen et al, 1996;Lukashevich et al, 1993;Childs and Peters, 1993]. Whether the mucosa simply serves to reduce the inoculum, to select attenuated variants, or to provide a protective immune response, it is clear that the mucosal route attenuates the infection substantially in comparison to the intravenous route.…”
Section: Subclinical Transient Mucosal Infection Of Rhesus Macaques Bmentioning
confidence: 99%
“…As suggested by murine experiments, ingestion of arenavirus [Rai et al, 1997] and of vectors expressing viral antigens [Djavani et al, 2000[Djavani et al, , 2001] provides immunity to lethal disease. Circumstantial evidence for mucosal immunity through virus ingestion comes from field observations: many individuals living in close contact with rodents and ingesting rodent-contaminated food are seropositive for Lassa virus but have never experienced Lassa fever disease [ter Meulen et al, 1996;Lukashevich et al, 1993;Childs and Peters, 1993]. Whether the mucosa simply serves to reduce the inoculum, to select attenuated variants, or to provide a protective immune response, it is clear that the mucosal route attenuates the infection substantially in comparison to the intravenous route.…”
Section: Subclinical Transient Mucosal Infection Of Rhesus Macaques Bmentioning
confidence: 99%
“…Lassa virus is carried primarily by the multimammate mouse Mastomys natalensis and causes up to 300,000 infections annually, of which approximately 30% result in disease varying from mild influenza-like illness to lethal hemorrhagic fever (HF) (23,38,40,41). It has been shown that hunting rodents and consuming their meat are major risk factors for rodent-to-human transmission (33,60). Our experimental studies with LCMV-infected mice (52,53) and monkeys (reference 35 and this study) indicate that oral inoculation leads to attenuated infections that occasionally cause disease.…”
mentioning
confidence: 99%
“…inoculation with high-dose LCMV-WE usually leads to subclinical infection, occasionally leads to disease, and rarely leads to death (I. S. Lukashevich et al, unpublished data). Taken together with the studies implicating consumption of rodents as a risk factor for infection, it is reasonable to propose that the mucosal route (via airways or the gastrointestinal tract) is a natural mode of virus transmission that could account for high levels of seropositive survivors in areas where Lassa virus is endemic (32,33,60).…”
mentioning
confidence: 99%
“…While the detection of a new positive IgG titer combined with an IgM response in the correct clinical setting may support a diagnosis of Lassa fever, the detection of a positive IgG response alone is insufficient to make a diagnosis. Lassa IgG titers may persist for decades (64), and seroprevalence studies in regions of endemicity have shown 4 to 55% of healthy individuals living in areas where the virus is endemic have detectable Lassa virus IgG titers (14,52,55,65,66).…”
Section: Antigen and Antibody Detection Assaysmentioning
confidence: 99%